Lecture 10: induction

Definitions

Definition: The power set of a set \(X\), written \(Pow(X)\) or \(2^X\) is the set of all subsets of \(X\).

For example,

Notation: If \(X\) and \(Y\) are sets, then \(X \setminus Y\) (pronounced "\(X\) minus \(Y\)") is the set of all elements of \(X\) that are not in \(Y\).

Induction

To demonstrate how induction works, we will prove that \(|Pow(X)| = 2^{|X|}\) for finite \(X\).

Big Claim: For all \(n \in \mathbb{N}\), if \(|X| = n\) then \(|Pow(X)| = 2^n\).

We start with a baby version:

Claim 0: If \(|X| = 0\) then \(|Pow(X)| = 2^0\).

Proof: If \(|X| = 0\), then \(X\) must be the empty set. \(Pow(\emptyset) = \{\emptyset\}\), which has \(1\) element. We are done since \(1 = 2^0\).

We'll prove the next claim in a more roundabout way for reasons that will become clear soon:

Claim 1: If \(|X| = 1\) then \(|Pow(X)| = 2^1\).

Proof: Since \(|X| = 1\), we can write \(X = \{x_1\}\). We can split \(Pow(X)\) into two groups of subsets: let \(A\) be the set of those that contain \(x_1\) and \(B\) be the set of those that don't. Formally, \(A = \{S \subseteq X \mid x_1 \in S\}\) and \(B = \{S \subseteq X \mid x_1 \notin S\}\).

Now, \(B\) is just the power set of \(X \setminus \{x_1\}\) (convince yourself with a small example). Since \(|X| = 1\), \(X \setminus \{x_1\}\) has cardinality 0. Therefore we can apply claim 0 to conclude that \(|B| = |Pow(X \setminus \{x_1\})| = 2^0\).

Moreover, \(|B| = |A|\), because the function \(f : B → A\) given by \(f(S) = S \cup \{x_1\}\) is a bijection (check this as an exercise).

So we have \(|Pow(X)| = |A \cup B| = |A| + |B| = 2^0 + 2^0 = 2 \cdot 2^0 = 2^1\) as required.

2 steps down, an infinite number to go. On to claim 2:

Claim 2: If \(|X| = 2\) then \(|Pow(X)| = 2^2\).

Proof: Since \(|X| = 2\), we can write \(X = \{x_1,\dots,x_2\}\). We can split \(Pow(X)\) into two groups of subsets: let \(A\) be the set of those that contain \(x_2\) and \(B\) be the set of those that don't. Formally, \(A = \{S \subseteq X \mid x_2 \in S\}\) and \(B = \{S \subseteq X \mid x_2 \notin S\}\).

Now, \(B\) is just the power set of \(X \setminus \{x_2\}\). Since \(|X| = 2\), \(X \setminus \{x_2\}\) has cardinality 1. Therefore we can apply claim 1 to conclude that \(|B| = |Pow(X \setminus \{x_2\})| = 2^1\).

Moreover, \(|B| = |A|\), because the function \(f : B → A\) given by \(f(S) = S \cup \{x_2\}\) is a bijection.

So we have \(|Pow(X)| = |A \cup B| = |A| + |B| = 2^1 + 2^1 = 2 \cdot 2^1 = 2^2\) as required.

There seems to be a pattern. Here's claim 3:

Claim 3: If \(|X| = 3\) then \(|Pow(X)| = 2^3\).

Proof: Since \(|X| = 3\), we can write \(X = \{x_1,\dots,x_3\}\). We can split \(Pow(X)\) into two groups of subsets: let \(A\) be the set of those that contain \(x_3\) and \(B\) be the set of those that don't. Formally, \(A = \{S \subseteq X \mid x_3 \in S\}\) and \(B = \{S \subseteq X \mid x_3 \notin S\}\).

Now, \(B\) is just the power set of \(X \setminus \{x_3\}\). Since \(|X| = 3\), \(X \setminus \{x_3\}\) has cardinality 2. Therefore we can apply claim 2 to conclude that \(|B| = |Pow(X \setminus \{x_3\})| = 2^2\).

Moreover, \(|B| = |A|\), because the function \(f : B → A\) given by \(f(S) = S \cup \{x_3\}\) is a bijection.

So we have \(|Pow(X)| = |A \cup B| = |A| + |B| = 2^2 + 2^2 = 2 \cdot 2^2 = 2^3\) as required.

At this point, you are probably convinced that we could use claim 3 to prove claim 4 (with almost exactly the same proof as the proof of claim 3), and we could use claim 4 to prove claim 5, and claim 5 to prove claim 6, and so on. In fact, for any \(N\), you could generate proofs of the claims all the way up to claim \(N\) using the following template:

Claim n: If \(|X| = n\) then \(|Pow(X)| = 2^n\).

Proof: Since \(|X| = n\), we can write \(X = \{x_1,\dots,x_n\}\). We can split \(Pow(X)\) into two groups of subsets: let \(A\) be the set of those that contain \(x_n\) and \(B\) be the set of those that don't. Formally, \(A = \{S \subseteq X \mid x_n \in S\}\) and \(B = \{S \subseteq X \mid x_n \notin S\}\).

Now, \(B\) is just the power set of \(X \setminus \{x_n\}\). Since \(|X| = n\), \(X \setminus \{x_n\}\) has cardinality n-1. Therefore we can apply claim (n-1) to conclude that \(|B| = |Pow(X \setminus \{x_n\})| = 2^{n-1}\).

Moreover, \(|B| = |A|\), because the function \(f : B → A\) given by \(f(S) = S \cup \{x_n\}\) is a bijection.

So we have \(|Pow(X)| = |A \cup B| = |A| + |B| = 2^{n-1} + 2^{n-1} = 2 \cdot 2^{n-1} = 2^n\) as required.

This is how a proof by induction works. To do a proof by induction:

Here is how I might put together the above pieces to prove the "big claim" if I were submitting it for a homework assignment, for example:

Big Claim: For all \(n \in \mathbb{N}\), if \(|X| = n\) then \(|Pow(X)| = 2^n\).

Proof: by induction. Let \(P(n)\) be the statement "if \(|X| = n\) then \(|Pow(X)| = 2^n\).

In the base case, we want to show \(P(0)\), i.e. if \(|X| = 0\) then \(|Pow(X)| = 2^0\). Well, if \(|X| = 0\), then \(X\) must be the empty set. \(Pow(\emptyset) = \{\emptyset\}\), which has \(1\) element. We are done since \(1 = 2^0\).

For the inductive step, fix an arbitrary \(n\) and assume \(P(n-1)\) holds. We want to show that if \(|X| = n\) then \(|Pow(X)| = 2^n\).

Since \(|X| = n\), we can write \(X = \{x_1,\dots,x_n\}\). We can split \(Pow(X)\) into two groups of subsets: let \(A\) be the set of those that contain \(x_n\) and \(B\) be the set of those that don't. Formally, \(A = \{S \subseteq X \mid x_n \in S\}\) and \(B = \{S \subseteq X \mid x_n \notin S\}\).

Now, \(B\) is just the power set of \(X \setminus \{x_n\}\). Since \(|X| = n\), \(X \setminus \{x_n\}\) has cardinality n-1. Therefore we can apply P(n-1) to conclude that \(|B| = |Pow(X \setminus \{x_n\})| = 2^{n-1}\).

Moreover, \(|B| = |A|\), because the function \(f : B → A\) given by \(f(S) = S \cup \{x_n\}\) is a bijection.

So we have \(|Pow(X)| = |A \cup B| = |A| + |B| = 2^{n-1} + 2^{n-1} = 2 \cdot 2^{n-1} = 2^n\), which completes the inductive step.

Therefore, by induction, for all \(n\), if \(|X| = n\) then \(|Pow(X)| = 2^n\).

Here is a second example of a proof by induction. Note that here we are assuming \(P(n)\) and proving \(P(n+1)\) in the inductive step. Either style (proving \(P(n) ⇒ P(n+1)\) or proving \(P(n-1) ⇒ P(n)\)) is fine: in each case you are showing how to reduce a complex case (either one of size \(n+1\) or one of size \(n\)) to a simpler case (either one of size \(n\) or one of size \(n-1\)).

Claim: for all \(n\), \(\sum_{i=0}^n i = \frac{n(n+1)}{2}\)

Proof: by induction. Let \(P(n)\) be the statement "\(\sum_{i=0}^n i = \frac{n(n+1)}{2}\)".

For the base case, we want to show \(P(0)\), i.e. that \(\sum_{i=0}^0 i = \frac{0(0+1)}{2}\). By inspection, both the left and right hand sides are 0, so \(P(0)\) holds.

For the inductive step, assume \(P(n)\); we wish to show \(P(n+1)\); that is, we want to show \(\sum_{i=0}^{n+1} i = \frac{(n+1)(n+2)}{2}\).

We simplify the left-hand side: \[\begin{aligned} \sum_{i=0}^{n+1} i &= (n+1) + \sum_{i=0}^n i && \text{by definition} \\ &= (n+1) + \frac{n(n+1)}{2} && \text{by $P(n)$} \\ &= \frac{2(n+1) + n(n+1)}{2} = \frac{(n+1)(n+2)}{2} && \text{by arithmetic} \\ \end{aligned}\] as required.

Therefore, by induction, \(\sum_{i=0}^n i = \frac{n(n+1)}{2}\) for all \(n\).